PENGUATAN LITERASI BAHASA INDONESIA MELALUI UKBI ADAPTIF DIGITAL UNTUK MGMP GURU BAHASA INDONESIA SMP DI KOTA BENGKULU - AFRODITA, MELI; Utomo, Padi; Chanafiah, Yayah; Utami, Mutiara Widya (Andromeda: Jurnal Pengabdian Masyarakat Rafflesia, 2025)
This community service activity aimed to enhance Indonesian language teachers’ understanding of digital literacy and the use of the Indonesian Language Proficiency Test (UKBI) Adaptive Digital as an instrument for strengthening literacy in schools. The activity was conducted at SMP Negeri 6 Bengkulu City on October 13, 2025, involving 27 teachers who are members of the Indonesian Language MGMP (Subject Teachers’ Forum) for junior high schools in Bengkulu City. The implementation consisted of three stages: preparation, implementation, and evaluation. During the implementation stage, participants attended presentations on digital literacy concepts, the UKBI Adaptive Digital system, and engaged in interactive discussions on how to apply UKBI results in Indonesian language teaching. The results indicated that the teachers demonstrated high enthusiasm and improved understanding of the importance of digital literacy as well as the function of UKBI as an objective and nationally standardized tool for measuring language proficiency. This activity also succeeded in fostering teachers’ motivation to carry out follow-up actions, including simulations and the actual administration of UKBI in the next stage of the program. Thus, this program contributes to strengthening teachers’ professional capacity in addressing the challenges of Indonesian language teaching in the digital assessment era. Keywords: language literacy; UKBI adaptive digital; Indonesian language teachers